Assessment of Soil Quality of Taluka Thari Mirwah, District Khairpur, Sindh, Pakistan - Shafqat Hussain Shar; Abdul Razak Mahar; Inyatullah Rajpar; Mumtaz Ali Saand; Ameer Ahmed Mirbahar; Khalil Ahmed Ansari; Rafat Saeed; Muzafar Hussain Sirohi (International Journal of Economic and Environmental Geology, 2018)
Soil salinity is an increasing threat for agriculture. The knowledge of physical and chemical properties of the soil is vital for the assessment of the capacity of soil for better plant productivity and improvement through management practices. We assessed the soil of ten union councils of Taulka Thari Mirwah, district Khairpur. The soil was evaluated for pH, EC, organic matter and salt contents through standardized methods. The overall soil was found to be slightly alkaline (pH 8 ± 0.6 SD), with a varied texture among the sites. The soil EC (10 ± 7.9 SD dS/m) was recorded to be comparatively higher than the surrounding districts. The study did not find any significant variation in various salt contents in the area. The organic contents were lower than the advised extent. However, the management practices were suggested to improve the health of soil for better productivity.